Developing General Cultural Competences: A Case Study of Students Taking a Course in Pedagogy and Psychology - Diana V. Pshenichnyuk (Peoples' Friendship University of Russia (RUDN University), 2021)
The education system and teachers are currently faced with the need to increase the interest of students not only in their chosen specialty and related training courses but in the content of the compulsory basic-level disciplines. One of the possible solutions to this problem may be filling such courses with practice-oriented and universal content, which can contribute to the formation and implementation of general cultural competences even in the learning (professional training) process. The purpose of the work is to present to the expert community the results of introducing the authors approach to the development of a set of knowledge, skills, abilities and competencies of students, as they are taught pedagogy and psychology, and to compare the process and results of face-to-face and online training conducted according to the authors program. The attention is focused on the development of practical skills and abilities within the framework of this course, in particular, the ability to conduct classes for peers with elements of training. The study used an adapted experimental curriculum of the pedagogy and psychology course, means of assessment (control works in the form of tests with open and closed questions) and self-assessment (authors questionnaire). The sample consisted of 68 undergraduate and postgraduate students of Lomonosov Moscow State University. The results of using the developed program showed high efficiency in relation to indicators of academic success of the students due to the creation of conditions for mutual learning and conducting classes by the students themselves.